Noninvasive patient fixation for extracranial stereotactic radiotherapy - Lohr, Frank; Debus, Jürgen; Frank, Claudia; Herfarth, Klaus; Pastyr, Otto; Rhein, Bernhard; Bahner, Malte Leonardo; Schlegel, Wolfgang; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 1999)
Purpose: To evaluate the setup accuracy that can be achieved with a novel noninvasive patient fixation technique based on a body cast attached to a recently developed stereotactic body frame during fractionated extracranial stereotactic radiotherapy. Methods and Materials: Thirty-one CT studies (≥ 20 slices, thickness: 3 mm) from 5 patients who were immobilized in a body cast attached to a stereotactic body frame for treatment of paramedullary tumors in the thoracic or lumbar spine were evaluated with respect to setup accuracy. The immobilization device consisted of a custom-made wrap-around body cast that extended from the neck to the thighs and a separate head mask, both made from Scotchcast. Each CT study was performed immediately before or after every second or third actual treatment fraction without repositioning the patient between CT and treatment. The stereotactic localization system was mounted and the isocenter as initially located stereotactically was marked with fiducials for each CT study. Deviation of the treated isocenter as compared to the planned position was measured in all three dimensions. Results: The immobilization device can be easily handled, attached to and removed from the stereotactic frame and thus enables treatment of multiple patients with the same stereotactic frame each day. Mean patient movements of 1.6 mm ± 1.2 mm (laterolateral [LL]), 1.4 mm ± 1.0 mm (anterior-posterior [AP]), 2.3 mm ± 1.3 mm (transversal vectorial error [VE]) and < slice thickness = 3 mm (craniocaudal [CC]) were recorded for the targets in the thoracic spine and 1.4 mm ± 1.0 mm (LL), 1.2 mm ± 0.7 mm (AP), 1.8 mm ± 1.2 mm (VE), and < 3 mm (CC) for the lumbar spine. The worst case deviation was 3.9 mm for the first patient with the target in the thoracic spine (in the LL direction). Combining those numbers (mean transversal VE for both locations and maximum CC error of 3 mm), the mean three-dimensional vectorial patient movement and thus the mean overall accuracy can be safely estimated to be ≤ 3.6 mm. Conclusion: The presented combination of a body cast and head mask system in a rigid stereotactic body frame ensures reliable noninvasive patient fixation for fractionated extracranial stereotactic radiotherapy and may enable dose escalation for less radioresponsive tumors that are near the spinal cord or otherwise critically located while minimizing the risk of late sequelae.
Gesehen am 19.02.2019